Tratamiento contable y tributario de los beneficios a empleados de las empresas comercializadoras de productos de primera necesidad - Zambrano Murillo, Christian Eduardo (2020)
The application of IAS 19 is highly important in companies that have a high number of workers, such as companies in the supermarket sector or the sale of necessities. This situation is increased when the employees complete certain years of service for the same employer, arising as a legal right, the so-called employer's retirement. Considering this, this research deals with the accounting and tax treatment of employee benefits of companies that market necessities, which seeks to analyze the accounting and tax incidence of employee benefits in the financial statements. of the companies that market basic necessities, for this the main theories in tax and financial matters will be based on the treatment of employee benefits, later the main errors in the accounting and tax treatment of employee benefits will be identified in the companies that market staple products to finally determine a guide for the correct accounting and tax treatment of employee benefits for marketers of staple products……..